2015
DOI: 10.1088/0004-637x/806/2/148
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated X-Ray, Ultraviolet, Optical, and Radio Observations of the PSR J1023+0038 System in a Low-Mass X-Ray Binary State

Abstract: The PSR J1023+0038 binary system hosts a neutron star and a low-mass, main-sequence-like star. It switches on year timescales between states as an eclipsing radio millisecond pulsar and a low-mass X-ray binary (LMXB). We present a multi-wavelength observational campaign of PSR J1023+0038 in its most recent LMXB state. Two long XMM-Newton observations reveal that the system spends ∼70% of the time in a ≈3 × 10 33 erg s −1 X-ray luminosity mode, which, as shown in Archibald et al., exhibits coherent X-ray pulsat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
112
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(127 citation statements)
references
References 67 publications
(152 reference statements)
14
112
0
Order By: Relevance
“…The system has been the subject of extensive multi-wavelength campaigns after its change of state (Halpern et al 2013;Kong 2013;Linares et al 2014;Patruno et al 2014;Takata et al 2014;Tendulkar et al 2014;Coti Zelati et al 2014;Deller et al 2015;Archibald et al 2015;Bogdanov et al 2015;Shahbaz et al 2015). Radio band observations performed by Deller et al (2015), in particular, showed a rapidly variable and flat spectrum that persisted over six months.…”
Section: Psr J1023+0038mentioning
confidence: 99%
“…The system has been the subject of extensive multi-wavelength campaigns after its change of state (Halpern et al 2013;Kong 2013;Linares et al 2014;Patruno et al 2014;Takata et al 2014;Tendulkar et al 2014;Coti Zelati et al 2014;Deller et al 2015;Archibald et al 2015;Bogdanov et al 2015;Shahbaz et al 2015). Radio band observations performed by Deller et al (2015), in particular, showed a rapidly variable and flat spectrum that persisted over six months.…”
Section: Psr J1023+0038mentioning
confidence: 99%
“…The J1023+0038 pulsar provides a useful test bed at a distance of 1.37 kpc toward the γ-ray source 2FGLJ1023.6+0040: an accretion disc was observed in the optical in 2000-2001; the detection of radio pulses from a MSP followed in 2007, until the pulses disappeared in 2013, quenched or eclipsed by the ionized flow from a new X-ray accretion disc [97,98,99]. The interaction between the pulsar magnetosphere/wind and the accretion disc is very dynamic, switching between different spectral states in X rays, with and without orbital modulation [98], and producing radio continuum emission and sporadic flares in the optical, UV, and X-rays, suggestive of propellor modes [97]. The γ-ray flux quintupled when the radio pulses disappeared [69,100].…”
Section: Millisecond Pulsar Arachnologymentioning
confidence: 99%
“…At the observed X-ray luminosity (a few ×10 33 erg s −1 ) accreting neutron stars only rarely show similar radio luminosities, and these systems are nearly all "transitional" millisecond pulsars that also show unusual, short-term X-ray and radio variability not seen in X9 (e.g. Bogdanov et al 2015;Deller et al 2015). Nonetheless, the phenomenology of accreting neutron stars at these X-ray luminosities is not well understood.…”
Section: Introduction X9 Is the Most Luminous (A Few × 10mentioning
confidence: 99%